The Effectiveness of Activities for Teaching EFL Writing in a Context of Vietnam - Nguyen, Duy Khang; Tuyet Van, Phan Thi; Anh Nguyet, Ly Thi (Journal of NELTA, 2012)
The article aims at pointing out what kinds of activities designed to improve the learners’ writing proficiency are effective in a Vietnamese context. With a two-group pretest and posttest design of an empirical research, the authors implemented a series of teaching activities in the classroom. The data were collected by means of pre-tests, post-tests, and interviews. The results indicated that the participants in the experimental condition significantly gained in their writing performance. Qualitative analysis of the data shows that the majority of participants positively evaluated the effectiveness of the activities. However, a consideration for contextual adjustment should be taken when several activities together might be overload to the learners. DOI: http://dx.doi.org/10.3126/nelta.v16i1-2.6132 NELTA 2011; 16(1-2): 82-96